Rancang Bangun Aplikasi Analisis Kepuasan Pengguna Layanan OPAC Pada Perpustakaan Universitas Dr. Soetomo - Ramadhani, Muchammad Andinouval; Sulistiowati, Sulistiowati; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Dr. Soetomo University(Unitomo) is one of the universities in Surabaya which has a library. One of the mission of Unitomo Library is to develop Unitomo Library with facilities and services based on technology and communication. In order to achieve this mission, the Unitomo Library should determine the level of user satisfaction of existing information technology services. So far, users still have not providing suggestions regarding existing services, due to lack of direction from the Library. Thus, the Unitomo Library has some difficulties in knowing the quality of information technology services till today. Based on the problems above, appears a need in the form of user satisfaction analysis applications with Service Quality method wherein Service Quality methods used to analyze the gap between expectation and reality which is accepted by the user. Existing processes in this application include validity test, reliability test, Service Quality calculation, and quadrant analysis. This application can store questionnaire data, perform validity test, reliability test, application can also do satisfaction analysis using Service Quality method. In addition, this application can also provide analysis results in the form of quadrant analysis and recommendations required by the library to develop OPAC services in the future.